Penguatan Tata Kelola Pendidikan Melalui Forum Konsultasi Publik: Strategi Penyusunan Rekomendasi Kebijakan di Dinas Pendidikan, Pemuda dan Olahraga Kabupaten Kebumen - Sotya Partiwi Ediwidjojo (Politeknik Piksi Ganesha Indonesia, 2026)
This article describes community service activities in the form of resource person participation in the Kebumen Regency Education Office Public Consultation Forum, which focuses on strengthening the New Public Service (NPS) paradigm in the provision of public services in the field of education. NPS emphasises the role of the government as a servant of the people, not a controller, and encourages collaboration between stakeholders. This activity aims to increase the understanding of education officials and the community about the principles of participatory, accountable, transparent, and responsive public services. The implementation methods include material presentations, interactive discussions, and the formulation of policy recommendations based on public values. The results of the activity show that digital transformation, equitable distribution of resources, and increased community participation are the three main pillars in realising quality education services. This forum produced seven improvement strategies that emphasise the importance of cross-sectoral synergy in improving the quality of educational services in Kebumen Regency.